Perceptions Of Pregnant Women In The Iii Trimester Regarding Preparation For Birth In Health Facilities And Twunan In The Politics Of Murano - Rofina Lamatokan; Erma Retnaningtyas; Retno Palupi Yonni Siwi; Nita Dwi Astikasari (Journal of Health Science Community, 2025)
Maternal mortality and infant mortality are indicators of good and bad health services in a country or region. The higher the maternal mortality rate indicates poor health services. One of the efforts made to reduce MMR is by encouraging every birth to be attended by trained health workers in health service facilities. The aim of this research was to determine the perceptions of pregnant women in the third trimester regarding preparation for childbirth in health facilities and traditional birth attendants at Polindes Murano. The research method used is a qualitative research method which is research on the conditions of natural objects where the researcher is the key instrument. The selection of research informants used the purposive method. There were 8 research informants, 5 key informants and 2 traditional shamans and 1 midwife.The research results showed that there were several informants who still chose to give birth at home with the help of midwives and traditional healers. There are several influencing factors, including distance from home and ancestral traditions. People trust shamans more because shamans are considered to have spiritual powers in assisting childbirth so that the birthing process runs smoothly. Traditional healers have known how to help with childbirth for generations. The midwife realizes that the beliefs held by the community at Polindes Murano cannot be changed in a short time, so the midwife hopes that the midwife can partner with the shaman in assisting with childbirth.Pregnant women can provide information about helpers and safe birthing places.